Partitioning of dissolved organic carbon, major elements, and trace metals during laboratory freezing of organic leachates from permafrost peatlands - Ivanova, Irina S.; Shirokova, Liudmila S.; Rols, Jean-Luc; Pokrovsky, Oleg S. (Applied sciences)
Climate change is likely to modify the freezing–thawing cycles in soils and surface waters of permafrost-affected and subarctic regions. However, the change of solution chemical composition during ice formation and the evolution of the remaining fluids remain very poorly known. Towards a better understanding of dissolved (<0.45 µm) organic carbon, as well as major and trace element behavior in permafrost peatland environments, here we performed laboratory freezing of peat leachates, from complete freezing to complete thawing, in order to quantify the partitioning of solutes between the aqueous solution and the remaining ice. Freezing experiments were conducted, with and without polyurethane insulation. Two main types of experiments involved (i) progressive freezing, when we started from liquid leachates (filtered <0.45 µm) and allowed them to freeze at −18 ◦C, and (ii) progressive thawing, where first, we froze solid a series of <0.45 µm filtered leachates and then monitored their thawing at room temperature, 20 ◦C. We hypothesized the existence of two main groups of solutes, behaving conservatively or non-conservatively during freezing, depending on their incorporation into the ice or their ability to coagulate in the form of insoluble minerals or amorphous materials in the fluid phase. An unexpected result of this work was that, despite a sizable degree of element concentration in the remaining fluid and possible coagulation of organic, organo-mineral, and inorganic compounds, the freezing and subsequent thawing produced final concentrations of most solutes which were not drastically different from the initial concentrations in the original leachates prior to freezing. This demonstrates the high stability of dissolved (<0.45 µm) organic carbon, iron, aluminum, and some trace metals to the repetitive freezing and thawing of surface waters in permafrost peatlands.